Electrochemically Exfoliated Graphite/Cu/Cu2O Composites and Their Photocatalytic Activity - Destiarti, Lia; Abdillah, Oktaviardi Bityasmawan; Maharsi, Retno; Floweri, Octia; Iskandar, Ferry (POSITRON, 2020)
In this work, the photocatalytic performance of electrochemically exfoliated graphite (EG) with low copper addition (â‰¤ 5 wt.%) was studied. Composites of EG/Cu/Cu2O were successfully prepared by microwave-assisted in situ reduction method. FTIR spectra of the samples showed that the main functional groups of graphite were detected in the samples. XRD characterization further proved the presence of EG, Cu, and Cu2O in the samples. The higher proportion of Cu2O presented in the samples prepared with a higher amount of Cu2+. SEM analysis showed that Cu2O/Cu particles were homogeneously deposited on the surface of EG. The composites of EG, Cu, and Cu2O with a varied amount of Cu (1 and 5 wt. %) in EG / Cu2+ mixture were examined as photocatalyst in the degradation process of Rhodamine B (RhB). The photocatalytic degradation of RhB was analysed by observing its decolorization within a set time of irradiation. UV-Vis analysis revealed that the degradation of RhB in EG/Cu/Cu2O A and B for 105 minutes was 26 and 35 %, respectively. The result demonstrates that the sample with a larger amount of Cu2O (sample B, Cu 5 wt.%) shows higher photocatalytic activity in the degradation of RhB.